P-18 End of life companionship: equipping volunteers with basic skills to offer support in the community. (19th November 2022) - Bassett, Lynn; Fong, Alejandra Dubeibe; Downey, John; Doherty, Margaret; Cornwall, Jon
Abstract : Background: The value of volunteer end-of-life companions has been recognised in hospitals and compassionate neighbourhood schemes (Hall & Meiton, 2019. BMJ Support Palliat Care. 9:229; Wilson, Justice, Thomas, et al., 2005. Health Serv Manage Res.18:244). Experience of people spending their last days in isolation during the COVID-19 pandemic intensified the call that no one should be left to die alone unless it is their wish (Ramos, Hashimoto & Henry, 2020. Int J Care Caring. 4:595). The End of Life Companionship project is a funded collaboration between the Centre for the Art of Dying Well at St Mary's University, Twickenham and the St Vincent de Paul Society, England and Wales (SVP) to equip SVP Members with basic companioning skills to support people nearing the end of life and their families. Aim: To provide End of Life Companionship training to 500 SVP Members during 2021-2022; to give them increased confidence to support dying beneficiaries, friends, and family members; to raise awareness of opportunities to volunteer as a companion in hospitals, hospices and community settings. Method: A three-hour online training course introduces the context of death and dying in the UK, spiritual values underpinning companionship, self-care and settings for companionship. Data from pre- and post-course surveys are analysed using a qualitative content analysis approach (Lindgren, Lundman, Graneheim, 2020. Int J Nurs Stud. 108: 103632) to gain understanding of changes in participants' perception of how it is to be with someone who is nearing the end of their life. In phase two of the evaluation, beneficiary experience of companionship will be explored using Transformative Evaluation (Cooper, 2014. The Learn Org. 21:146). Results: In the year to April 2022, 176 participants completed the course. Initial analysis of the first 90 surveys shows that 64 participants identified changes in themselves including feeling of reassurance, reduced fear of death and better understanding of the qualities needed to be a companion. 19 participants, who mostly had previous experience of end-of-life accompaniment, described no change in perception but they reported heightened awareness and/or that the course has broadened their knowledge.